2021
DOI: 10.5937/fme2101147o
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flow in trapezoidal labyrinth-channels of drip irrigation

Abstract: The clogging of emitters has been considered as one of the most troublesome problems inhibiting the extension of drip irrigation. This paper investigates the flow field of water and behaviour of suspended particles in the trapezoidal labyrinth-channel. Computational Fluid Dynamics methods has been executed on liquid-solid two-phase flow in labyrinth-channel emitters. RNG k-e turbulence model was used to evaluate four types of emitters that have the same characteristics and differ in the elbow width S. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Several investigations have been based on the numerical study of the flow behavior in emitters (Wei et al, 2009). They found that, at the emitter level, the areas where particles can be deposited are the low flow velocity areas, the corners, and the vortex areas (Ouarriche et al, 2021; Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been based on the numerical study of the flow behavior in emitters (Wei et al, 2009). They found that, at the emitter level, the areas where particles can be deposited are the low flow velocity areas, the corners, and the vortex areas (Ouarriche et al, 2021; Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Como descrito anteriormente, a Figura 52C possibilita a visualização da região de estagnação, onde as partículas foram encontradas e, provavelmente, podem ter iniciado a sedimentação ao longo do labirinto da maioria dos emissores do Modelo 2 avaliado para cima. Esse cenário possivelmente tem relação com a força de arraste e a força inercial ocorrendo nas partículas dentro do labirinto, sendo que a força inercial é proporcional ao diâmetro da partícula e a força de arraste segue uma relação com o quadrado do tamanho da partícula, ou seja, à medida que os diâmetros das partículas se tornam maiores essas tendem a sair da zona de fluxo principal e entrar nas zonas de vórtices (OUARRICHE et al, 2021).…”
Section: Modelo 2 Com Inserção Para Cimaunclassified